Assessing the Extinction Probability of the Purple-winged Ground Dove, an Enigmatic Bamboo Specialist - Lees, Alexander C.; Devenish, Christian; Areta, Juan Ignacio; de Araújo, Carlos Barros; Keller, Carlos; Phalan, Ben; Silveira, Luís Fábio (Frontiers in Ecology and Evolution, 2021)
The continued loss, fragmentation, and degradation of forest habitats is driving an extinction crisis for tropical and subtropical bird species. This loss is particularly acute in the Atlantic Forest of South America, where it is unclear whether several endemic bird species are extinct or extant. We collate and model spatiotemporal distributional data for one such ‘lost’ species, the Purple-winged Ground Dove Paraclaravis geoffroyi, a Critically Endangered endemic of the Atlantic Forest biome, which is nomadic and apparently dependent on masting bamboo stands. We compare its patterns of occurrence with that of a rare ‘control’ forest pigeon, the Violaceous Quail-Dove Geotrygon violacea, which occurs in regional sympatry. We also solicit information from aviculturists who formerly kept the species. We find that the two species share a similar historical recording rate but can find no documentary evidence (i.e. specimens, photos, video, sound recordings) for the persistence of Purple-winged Ground Dove in the wild after the 1980s, despite periodic sighting records, and after which time citizen scientists frequently documented the control species in the wild. Assessments of the probability that the species is extant are sensitive to the method of analysis, and whether records lacking documentary evidence are considered credible. Analysis of the temporal sequence of past records reveals the extent of the historical range contraction of the Purple-winged Ground Dove, while our species distribution model highlights the geographic search priorities for field ornithologists hoping to rediscover the species - aided by the first recording of the species vocalizations which we obtained from interviews with aviculturists. Our interviews also revealed that the species persisted in captivity from the 1970s until the 1990s (up to 150 birds), until a law was passed obstructing captive breeding efforts by private individuals, putting an end to perhaps the best chance we had to save the species from extinction.